The Degree of Using Alternative Assessment Strategies before and during COVID- 19 among Female Faculty Members at Bisha University - Ali, Nadia Muhammad (Journal of Educational and Psychological Sciences, 2021)
The study aimed to explore the degree of using alternative assessment strategies before and during Covid-19 among faculty members at Bisha University. It also aimed to find out the significant differences in using alternative assessment strategies attributed to the variables of before and during Covid-19, experience and specialization. To achieve the study objective، the descriptive method was used. The society of the study consisted of faculty members of Art and Education colleges. The sample of the study was selected by random method and consisted of (64) faculty members from the colleges of Art and Education at Bisha University. A questionnaire of (24) strategies was prepared and distributed on five domains of alternative assessment: first, performance, second, the writing assessment, third, the observation, fourth, the communication, and fifth, the core self. The final tool of the questionnaire consisted of (22) paragraphs as two paragraphs were deleted from the questionnaire for insuring the reliability standards.The results of the study showed that the strategies of presentation, discussion in the field of (performance-based evaluation) and objective tests, working papers in the field of evaluation (based on paper and pen), forums, group work in the field of evaluation (based on communication), projects and an achievement file The student in the field of alternative evaluation (self-reliant) won the first place, and the second consecutively in each subject area, and the results showed positive differences in favor of members ’use of alternative evaluation strategies during the Corona pandemic. As for the differences between strategies before and during the pandemic, as well as experience and specialization, did not show any significance. strategies distributed on four domains of alternative assessment after checking the validity and reliability. The results of the study showed that the experimental average of the degree of using alternative evaluation strategies before the Corona pandemic was (9.57), while the average during it was (11.109). Also, the following strategies; presentation and discussion in the first domain, objective tests and work sheet in the second domain, group working and forums in the third domain and projects and portfolio in the fourth domain came in the first rank. Moreover، the results indicated that there were no significant differences among faculty members attributed to the variables of before and during Covid-19, experience and specialization.According to the study findings, the most important recommendation was that the alternative assessment strategies should be used by the faculty members at Bisha University and should be included in each course specification. Based on these findings, suggestions for future studies were recommended such as" Barriers to using alternative assessment strategies and measure the level of using alternative assessment strategies before and during Covid-19 among faculty members attributed to the same variables.
Keywords: Alternative Assessment Strategies; Covid-19; Female Faculty Members; Bisha University